Conquête d’un milieu, adaptation à une multitude de réalités : l’exemple de la conquête romaine des espaces oasiens égyptiens - Evelyne Ferron (Conserveries Mémorielles)
Even if the Western desert of Egypt is considered one of the most hyper-arid in the world, five oases are nonetheless inhabitable, even though they are situated far from the Nile Valley. The archaeological diggings started late in this area, but because of the quantity of artefacts and documents available for the Roman period, it allows now historians specialised in Roman history to study the oases during Roman occupation. Integrated to Egypt since Pharaonic times, and then integrated to the Roman Empire at the end of the 1st century BC, people living in the oases experienced a major agricultural and economical development during Roman era. The main objective of this article is to study the migration of Roman administrators in the oases of Egypt, focusing more specifically on the strategies of adaptation of the Roman power to some of the oasian particularities.